THE INFLUENCE OF HEALTH EDUCATION REGARDING PERSONAL HYGIENE DURING MENSTRUATION ON BEHAVIOR OF ADOLESCENT GIRLS - Umsapyat, Fitrianda; Puspita, Enny; Sholikhah, Dwi Uswatun (Library Unit collaborates with the Institute for Research and Community Service, College of Health Sciences Husada Jombang, 2025)
Background: Menstrual hygiene management is a public health concern, particularly among adolescent girls. Objectives: This study aimed to evaluate the impact of health education on personal hygiene during menstruation on behavioral changes among adolescent girls at SMAN 1 Jombang. Methods: A quasi-experimental study with a one-group pretest-posttest design was conducted in March 2024. Sixty-five female students from grades X1 to X4 were selected through total sampling. Health education was delivered using leaflets, videos, and WhatsApp messages. Data were collected using validated questionnaires before and after the intervention. The Wilcoxon signed-rank test was used for data analysis. Results: 55% of participants exhibited negative hygiene behavior before the intervention. Post-intervention, 100% showed improved, positive behavior. The Wilcoxon test showed a statistically significant effect (p < 0.05). Conclusion: Health education significantly improved menstrual hygiene practices among the participants. Schools should incorporate menstrual hygiene education through the School Health Unit (UKS).